Answer:
(nearest tenth)
Step-by-step explanation:
Given the distance formula,
, distance between (-4, 5) and (4, 0) is calculated as follows:
Let ![(-4, 5) = (x_1, y_1)](https://tex.z-dn.net/?f=%20%28-4%2C%205%29%20%3D%20%28x_1%2C%20y_1%29%20)
![(4, 0) = (x_2, y_2)](https://tex.z-dn.net/?f=%20%284%2C%200%29%20%3D%20%28x_2%2C%20y_2%29%20)
![d = \sqrt{(4 - (-4))^2 + (0 - 5)^2}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B%284%20-%20%28-4%29%29%5E2%20%2B%20%280%20-%205%29%5E2%7D%20)
![d = \sqrt{(8)^2 + (- 5)^2}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B%288%29%5E2%20%2B%20%28-%205%29%5E2%7D%20)
![d = \sqrt{64 + 25}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B64%20%2B%2025%7D%20)
![d = \sqrt{89}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B89%7D%20)
(nearest tenth)
Answer: {5 ± 2√10, 5 - 2√10}
Step-by-step explanation: First isolate the binomial squared by adding 40 to both sides to get (x - 5)² = 40.
Next, square root both sides to get x - 5 = ± √40.
Notice that root of 40 can be broken down to 2√10.
So we have x - 5 = ± 2√10.
To get <em>x</em> by itself, add 5 to both sides to get x = 5 ± 2√10.
So our answer is just {5 ± 2√10, 5 - 2√10}.
As a matter of form, the number will always come before the
radical term in your answer to these types of problems.
In other words, we use 5 ± 2√10 instead of ± 2√10 + 5.
Answer:
x = 1/2QN^2
Step-by-step explanation:
The acceleration of the particle is given by the formula mentioned below:
![a=\frac{d^2s}{dt^2}](https://tex.z-dn.net/?f=a%3D%5Cfrac%7Bd%5E2s%7D%7Bdt%5E2%7D)
Differentiate the position vector with respect to t.
![\begin{gathered} \frac{ds(t)}{dt}=\frac{d}{dt}\sqrt[]{\mleft(t^3+1\mright)} \\ =-\frac{1}{2}(t^3+1)^{-\frac{1}{2}}\times3t^2 \\ =\frac{3}{2}\frac{t^2}{\sqrt{(t^3+1)}} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7Bds%28t%29%7D%7Bdt%7D%3D%5Cfrac%7Bd%7D%7Bdt%7D%5Csqrt%5B%5D%7B%5Cmleft%28t%5E3%2B1%5Cmright%29%7D%20%5C%5C%20%3D-%5Cfrac%7B1%7D%7B2%7D%28t%5E3%2B1%29%5E%7B-%5Cfrac%7B1%7D%7B2%7D%7D%5Ctimes3t%5E2%20%5C%5C%20%3D%5Cfrac%7B3%7D%7B2%7D%5Cfrac%7Bt%5E2%7D%7B%5Csqrt%7B%28t%5E3%2B1%29%7D%7D%20%5Cend%7Bgathered%7D)
Differentiate both sides of the obtained equation with respect to t.
![\begin{gathered} \frac{d^2s(t)}{dx^2}=\frac{3}{2}(\frac{2t}{\sqrt[]{(t^3+1)}}+t^2(-\frac{3}{2})\times\frac{1}{(t^3+1)^{\frac{3}{2}}}) \\ =\frac{3t}{\sqrt[]{(t^3+1)}}-\frac{9}{4}\frac{t^2}{(t^3+1)^{\frac{3}{2}}} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7Bd%5E2s%28t%29%7D%7Bdx%5E2%7D%3D%5Cfrac%7B3%7D%7B2%7D%28%5Cfrac%7B2t%7D%7B%5Csqrt%5B%5D%7B%28t%5E3%2B1%29%7D%7D%2Bt%5E2%28-%5Cfrac%7B3%7D%7B2%7D%29%5Ctimes%5Cfrac%7B1%7D%7B%28t%5E3%2B1%29%5E%7B%5Cfrac%7B3%7D%7B2%7D%7D%7D%29%20%5C%5C%20%3D%5Cfrac%7B3t%7D%7B%5Csqrt%5B%5D%7B%28t%5E3%2B1%29%7D%7D-%5Cfrac%7B9%7D%7B4%7D%5Cfrac%7Bt%5E2%7D%7B%28t%5E3%2B1%29%5E%7B%5Cfrac%7B3%7D%7B2%7D%7D%7D%20%5Cend%7Bgathered%7D)
Substitute t=2 in the above equation to obtain the acceleration of the particle at 2 seconds.
![\begin{gathered} a(t=1)=\frac{3}{\sqrt[]{2}}-\frac{9}{4\times2^{\frac{3}{2}}} \\ =1.32ft/sec^2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20a%28t%3D1%29%3D%5Cfrac%7B3%7D%7B%5Csqrt%5B%5D%7B2%7D%7D-%5Cfrac%7B9%7D%7B4%5Ctimes2%5E%7B%5Cfrac%7B3%7D%7B2%7D%7D%7D%20%5C%5C%20%3D1.32ft%2Fsec%5E2%20%5Cend%7Bgathered%7D)
The initial position is obtained at t=0. Substitute t=0 in the given position function.